A novel method for fast enrichment and monitoring of hexavalent and trivalent chromium at the ppt level with modified silica MCM-41 and its determination by inductively coupled plasma optical emission spectrometry - Mohammad Reza Ganjali; Leila Hajiagha Babaei; Alireza Badiei; Kamal Saberian; Seiedmahmoudreza Behbahani; Ghodsi Mohammadi Ziarani; Masoud Salavati- Niasari (Química Nova, 2006)
Chromium(III) at the ng L-1 level was extracted using partially silylated MCM-41 modified by a tetraazamacrocyclic compound (TAMC) and determined by inductively coupled plasma optical emision spectrometry (ICP OES). The extraction time and efficiency, pH and flow rate, type and minimum amount of stripping acid, and break- through volume were investigated. The method's enrichment factor and detection limit are 300 and 45.5 pg mL-1, respectively. The maximum capacity of the 10 mg of modified silylated MCM-41 was found to be 400.5±4.7 µg for Cr(III). The method was applied to the determination of Cr(III) and Cr(VI) in the wastewater of the chromium electroplating industry and in environmental and biological samples (black tea, hot and black pepper).